2018
DOI: 10.1038/s41598-018-31296-7
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of topological nodal-line fermionic phase in a magnetic material GdSbTe

Abstract: Topological Dirac semimetals with accidental band touching between conduction and valence bands protected by time reversal and inversion symmetry are at the frontier of modern condensed matter research. A majority of discovered topological semimetals are nonmagnetic and conserve time reversal symmetry. Here we report the experimental discovery of an antiferromagnetic topological nodal-line semimetallic state in GdSbTe using angle-resolved photoemission spectroscopy. Our systematic study reveals the detailed el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 52 publications
12
88
0
Order By: Relevance
“…The superstructure evolution of GdSb x Te 2− x−δ is related to the magnetic property change, for example, the minimum Néel transition temperature is observed near the commensurate‐to‐incommensurate transition boundary ( x = 0.21). We would like to point out that the previously investigated TSM “GdSbTe” in fact possesses out‐of‐plane lattice parameter and magnetic properties resembling those of GdSb 0.54 Te 1.44 reported in this work. Since the crystals for the study mentioned above were also grown by vapor transport, it is not surprising that off‐stoichiometric samples were synthesized, as all our attempts to synthesize stoichiometric GdSbTe with vapor transport failed.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The superstructure evolution of GdSb x Te 2− x−δ is related to the magnetic property change, for example, the minimum Néel transition temperature is observed near the commensurate‐to‐incommensurate transition boundary ( x = 0.21). We would like to point out that the previously investigated TSM “GdSbTe” in fact possesses out‐of‐plane lattice parameter and magnetic properties resembling those of GdSb 0.54 Te 1.44 reported in this work. Since the crystals for the study mentioned above were also grown by vapor transport, it is not surprising that off‐stoichiometric samples were synthesized, as all our attempts to synthesize stoichiometric GdSbTe with vapor transport failed.…”
Section: Discussionsupporting
confidence: 59%
“…This is well‐documented in rare‐earth tritelluride systems . For the GdSb x Te 2− x−δ system it can be inferred from the previously mentioned ARPES study that the Fermi surface also does not fully gap. Recently, we have reported that the very small Fermi surface pockets, which result from a CDW‐induced Fermi surface reconstruction in GdTe 3, exhibit very high mobility and a light effective mass .…”
Section: Gdsbxte2−x−δ Crystal Structuresmentioning
confidence: 78%
See 1 more Smart Citation
“…[25] In this context, LnSbTe materials (Ln = lanthanide) that are isostructural and isoelectronic to ZrSiS have been suggested as promising candidates as magnetic TSMs. [28][29][30][31][32][33] However, the band structure of these materials is not as "clean" as in ZrSiS: the FS contains trivial pockets, in addition to the nodal-line states.…”
Section: Introductionmentioning
confidence: 99%
“…The compounds in the yellow region are mostly established TSMs, for example ZrSiS and related compounds with M=Zr or Hf, X=Si, Ge, or Sn, and Z=O, S, Se, or Te 29,[47][48][49][50][51]. Other noteworthy compounds in the region are the LnSbTe family (Ln = lanthanide) [52][53][54][55]. On the zone border lies the topological superconductor UTe 2 [56][57][58].…”
mentioning
confidence: 99%